Developing of Bi-Sn eutectic alloy with in additions for glass sealing - (:unkn) unknown (My University, 2012)
In this study, bismuth-tin (Bi-Sn) eutectic compositions with varying additions of indium are investigated for their joining strength on borosilicate glass substrate. Characterization of solder alloys was carried out using differential scanning calorimeter, x-ray diffraction, electron dispersive spectrograph and scanning electron microscope. Sessile-drop testing was used to understand wetting ability of the solder alloys on the substrate. Shear stress testing was used to investigate mechanical behavior of the solder alloys and the data was plotted. Copyright 2012 ASM International® All rights reserved.